Botulinum toxin and eyelid ptosis: A narrative review (Research, Society and Development, 2024)
Botulinum toxin type A (BoNT-A) is widely used in aesthetic and therapeutic procedures, being one of the most effective interventions for smoothing expression lines. However, one of the potential adverse effects is eyelid ptosis, which refers to the drooping of the upper eyelid due to the unintended diffusion of the toxin to the levator palpebrae muscle. This effect, although temporary, can cause both aesthetic and functional discomfort for patients. The proposed narrative review aims to comprehensively examine the literature on the association between the use of botulinum toxin and eyelid ptosis, identifying risk factors, the mechanisms of action involved, and strategies to mitigate this complication. By addressing these issues, the goal is to provide a thorough understanding for professionals using BoNT-A in their practices, in order to improve the safety and efficacy of the procedure. The review also aims to identify gaps in current research and suggest directions for future investigations on how to prevent eyelid ptosis, ensuring greater patient satisfaction.